The outsourcing of household tasks and labour contract in domestic work - Suleman, F. (2012)
This paper empirically illustrates that flexible work arrangements may be found unsuitable for outsourcing certain household tasks. For this purpose we analyse the relationship between tasks performed by domestic workers and the nature of the labour contract. Our study draws on a dataset from a sample of Portuguese domestic workers, and uses a fuzzy clustering approach to identify bundles of tasks together with contract features. The results achieved suggest a segmentation of domestic workers into four groups: two comprising carers, who enjoy a standard type of contract, and another two groups of cleaners with flexible and informal work arrangements. However, there is no distinct boundary between these groups. The overlapping that occurs between tasks and contracts justifies the use of the fuzzy approach to data analysis.